Phosphate-Solubilizing Fungi and Alkaline Phosphatase Trigger the P Solubilization During the Co-composting of Sorghum Straw Residues With Burkina Faso Phosphate Rock - Sarr, Papa Saliou; Tibiri, Ezechiel Bionimian; Fukuda, Monrawee; Zongo, Armel Nongma; Compaore, Emmanuel; Nakamura, Satoshi (Frontiers in Environmental Science, 2020)
Phosphate rocks (PR), the primary source of phosphorus (P), are often co-composted with organic materials to enhance P availability. However, the mechanisms of P solubilization in PR-enriched composts are not well elucidated. This study investigated such mechanisms by monitoring the changes in P fractions during composting and by determining the relationships between the physicochemical and biological parameters. Sorghum straw residues were composted alone (Comp), or with 10% PR (P-Comp), or with 10% PR and 10% rhizosphere soil (P-Comp-Soil), and samples were collected at 45, 60, and 180 days for analysis. The labile-P composed of H2O- and NaHCO3-extractable inorganic P (Pi) and organic P (Po), the moderately labile-P extracted by NaOH (Pi + Po), and the unavailable P formed of the HCl-P and residual-P, increased with the progress of the composting. At 180 days, P-Comp-Soil contained the highest amount of labile-P. There were strong and positive correlations between labile-P and the abundance of total fungi, phosphate-solubilizing fungi (PSF), alkaline phosphatase phoD, phosphonatase phnX, acid phosphatase aphA. Although total fungi were much fewer than total bacteria, the PSF mainly triggered the mineral P solubilization. The alkaline phosphatase phoD was the main enzyme leading the organic P mineralization, while the contribution of phosphonatase phnX, acid phosphatase aphA, and siderophore entA to the organic P solubilization was minor. Besides, the bacterial specific-transporter (pstS) gene increased with the increase of labile-P, allowing for immobilization of little fractions of P in microbial cells. This study highlighted the significant role of PSF and alkaline phosphatase in the P solubilization of PR-enriched composts. Furthermore, it showed the benefit of supplementing the PR-enriched composts with rhizosphere soil, a niche of ecologically important source of beneficial microbes.